The legal analysis of money laundering and financing terrorism legislation in Malaysia and Yemen - Alkhazzan, Najlaa Abdulrahman (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
Money laundering is the process used to hide the original source of the proceeds, which are gained from illegal activities by many complicated transactions. As a result of that, the dirty money will reappear in legitimate form. Money laundering and terrorism financing crimes have become a global issue nowadays and threaten the function of the financial and economic system. Malaysia and Yemen, like other countries, are also concerned with this and spend a lot of effort to combat these crimes. However, studies show that these crimes are still increasing year after year. This study aims to find out the reasons for the continuity of these crimes despite the existence of laws, international treaties and cooperation among the various countries to combat this crime of money laundering and terrorism financing. Many studies have been done with regard to money-laundering and financing of terrorism but all these studies discussed it from different perspectives and no study discusses the existing laws prevailing in both Malaysia and Yemen to find the loopholes and strengths in these laws. As a result of that, this thesis focuses on the prevailing laws in Malaysia and Yemen and analyses the provisions of AMLAFTA 2001 in Malaysia and AMLATF 2010 in Yemen, by using qualitative approach method to obtain good results. The study found that the two pieces of legislation on anti-money laundering and counter financing terrorism (AML/CFT) in Malaysia and Yemen seems to be, to a great extent, in pari materia to one another as they originated from the same source, namely the Financial Action Task Force's (FATF) Forty Recommendations.. The study also gives some recommendations toward further improving and upgrading the existing AMLATFA in Malaysia and AMLATF in Yemen.